Assessment of ecological health of Swarnamukhi river estuary, southeast coast of India, through AMBI indices and multivariate tools. (March 2021) - Pandey, Vikas; Venkatnarayanan, S.; Kumar, P. Sathish; Ratnam, Krupa; Jha, Dilip Kumar; Rajaguru, S.; Dharani, G.
Abstract: A combination of biotic indices, geo-accumulation (Igeo ) index, and a multivariate approach were applied to assess the anthropogenic influence on the benthic community at five stations from 2018 to 2019 in the Swarnamukhi river estuary, Nellore, India. Non-metric multidimensional scaling and cluster analysis indicated that the Buckingham canal (BC) station showed azoic conditions and formed a separate cluster. Strong positive factor loadings of Cd (0.96), Al (0.93), Zn (0.91), Fe (0.90), Co (0.89), Cu (0.89), Ni (0.87), Pb (0.85), Cr (0.77), organic matter (0.94), Silt (0.92), and clay (0.93) and negative loading of sand (−0.90) showed the variability in sediment. AMBI results illustrated the disturbance status of each station and classified BC station as 'extremely disturbed' class, and M-AMBI assessed the ecological status as 'bad'. The Igeo index also revealed metal (Cd) contamination. The present study illustrated that the combined approach is effective for ecological assessment of coastal ecosystem. Highlights: BC station was azoic and formed a separate cluster as per the nMDS and CA. AMBI results classified BC station as an 'extremely disturbed' class. M-AMBI results described ecological status as 'bad' at BC. Higher concentrations of OM and metals showed deteriorating effects on macrofauna.